DIGITAL TRANSFORMATION AND PRODUCTIVITY - Jovevski, Dimitar; Drakulevski, LJubomir; Firfov, O (KNOWLEDGE - International Journal - Knowledge - Capital of the Future, 2023)
Due to the impact of the digital revolution, there has been a notable elevation in standards across the board. Furthermore, the recent challenges posed by the pandemic have further complicated the intricate landscape of the business world. This realm gives rise to a multitude of diverse discussions, yet remains a topic commonly deliberated among scholars with a focus on productivity perspectives. While research papers on Digital Transformation have undergone progressive development over time, their quantity has witnessed a significant surge only recently. This scholarly article makes reference to pertinent scientific contributions spanning various tiers, accentuating and immersing within the context of North Macedonia. The research delves into the components of digital transformation, encompassing facets pertaining to the magnitude of information and communication, nuances of business modeling, and enhancements of business processes. Notably, the success of Digital Transformation is heavily contingent upon modifications in process and operations management. It is crucial to recognize that merely incorporating information technology is insufficient for effecting IT-enabled changes.The empirical analysis embraced a dual-phase approach involving consecutive rounds of questionnaires. The initial phase centered around closed-ended questions, while the subsequent phase involved interviews featuring open-ended inquiries. The results were subject to both quantitative and qualitative assessment, drawing insights from a diverse array of industries. These insights pertained to their digital transformation processes, predominantly aligning with respondents' perceptions of productivity. In this vein, the research endeavor seeks to make a geographical contribution by identifying variables associated with the digitalization or digital transformation processes within companies situated in North Macedonia. The findings imply that there is a biased response from various stakeholders, indicating a modest correlation between the process of change and productivity. As the process of digitalization necessitates a certain degree of change, it can be inferred that digitalization potentially exerts specific effects on productivity.
Keywords: Digital transformation, Productivity, Management, Organization